2010
DOI: 10.2169/internalmedicine.49.2785
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Cerebellar Atrophy Using Voxel-based Morphometry and SPECT with an Easy Z-score Imaging System

Abstract: Objective With conventional MRI and single-photon emission computed tomography (SPECT),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
1
5
0
1
Order By: Relevance
“…It has been reported that while the frequency of gait ataxia in patients with cerebellar ataxia with GAD-Ab was 95%, the frequency of dysarthria in those was 66% ( 4 ). In addition, this disease did not necessarily show a reduced perfusion in the cerebellar region by SPECT, such as was seen in the present case ( 17 ). These findings suggested the possibility that cases of cerebellar ataxia with GAD-Ab manifested more advanced dysfunction in cerebellar vermis than cerebellar hemisphere.…”
Section: Discussionsupporting
confidence: 56%
“…It has been reported that while the frequency of gait ataxia in patients with cerebellar ataxia with GAD-Ab was 95%, the frequency of dysarthria in those was 66% ( 4 ). In addition, this disease did not necessarily show a reduced perfusion in the cerebellar region by SPECT, such as was seen in the present case ( 17 ). These findings suggested the possibility that cases of cerebellar ataxia with GAD-Ab manifested more advanced dysfunction in cerebellar vermis than cerebellar hemisphere.…”
Section: Discussionsupporting
confidence: 56%
“…To address whether these changes were localized across the vermis, we compared the cell density in anterior and posterior lobules in SCA6 84Q/84Q mice, and found no significant differences at 2 years (anterior, 3.7 ± 0.19 cells/100 μm; posterior, 4.2 ± 0.25 cells/100 μm; p = 0.51). Rather, we observed a reduced Purkinje cell density in both anterior and posterior lobules of SCA6 84Q/84Q mice at 2 years compared with age- and litter-matched WT mice (anterior: F (3,92) = 10.16; p < 0.0001; posterior: F (3,106) = 3.37; p = 0.02; data not shown), in contrast to the predominantly anterior Purkinje cell degeneration observed in some human SCA6 patients ( Gierga et al, 2009 ; Nanri et al, 2010 ).…”
Section: Resultsmentioning
confidence: 84%
“…7 A , B ), which is consistent with previous reports ( Watase et al, 2008 ). We wondered whether subtle changes in Purkinje cell numbers or morphology might be restricted to only part of the cerebellum, since Purkinje cell degeneration has been reported to be more prevalent in anterior lobules of cerebellar vermis in some human patients ( Gierga et al, 2009 ; Nanri et al, 2010 ). To address whether changes might be localized to subregions of the cerebellar vermis, we measured Purkinje cell density in anterior and posterior lobules, but observed no significant differences in both WT and SCA6 84Q/84Q mice (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…SCA-6 is a slowly progressive, genetic neurodegenerative condition where damage is restricted to the Purkinje cells of the cerebellum (Zhuchenko et al, 1997). The degeneration is characterised by a stereotyped, dorso-ventral progression in the cerebellar cortex (Butteriss, Chinnery, & Burchall, 2005), with usually no significant white matter loss or degeneration in extracerebellar areas including cortical areas (Ishikawa et al, 1999; Lukas et al, 2006; Nanri et al, 2010; Schlos et al, 1998; Schulz et al, 2010; Zhuchenko et al, 1997). Interpretation of previous studies has been limited by the use of heterogeneous patient groups with lesions (especially strokes) in which the cerebellum is not affected in the same way across patients, and where extracerebellar damage may also occur.…”
Section: Introductionmentioning
confidence: 99%